2021
DOI: 10.3389/fpsyg.2021.715146
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Mindfulness-Based Intervention Programs at Work on Psychological Wellbeing and Work Engagement

Abstract: Two different mindfulness-based interventions were deployed in a sample of white-collar workers to explore the differential effects on different facets of mindfulness, dimensions of psychological wellbeing, work engagement, performance, and stress of a participant. A total of 28 participants completed one of the different programs, and their results were compared between groups and against 27 participants randomly allocated to a waiting list control group. Results suggest both mindfulness intervention programs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 57 publications
2
3
0
Order By: Relevance
“…Although there is not enough empirical evidence for any specific psychological interventions in the workplace [8], our results are in line with the evidence that workplace MBIs decrease burnout and stress levels and have other positive effects on mental health [32][33][34]. Further research should explain how these effects are produced, i.e., which are the involved mechanisms of action [9].…”
Section: Discussionsupporting
confidence: 83%
“…Although there is not enough empirical evidence for any specific psychological interventions in the workplace [8], our results are in line with the evidence that workplace MBIs decrease burnout and stress levels and have other positive effects on mental health [32][33][34]. Further research should explain how these effects are produced, i.e., which are the involved mechanisms of action [9].…”
Section: Discussionsupporting
confidence: 83%
“…They also may be easily distracted as a result of workload that occurs in the working environment and feeling of dissatisfaction. (Calcagni et al, 2021) The present finding results displayed correlation between total head nurses perceived mindfulness and total innovative work behavior among nurses. There was a highly positive statistical significant correlation between total head nurses' perceived of mindfulness and total perceived innovative work behavior among staff nurses.…”
Section: Statistical Analysis Of Resultssupporting
confidence: 60%
“…Mindfulness manifests internal resource abundance and has statistical significance on work engagement. Calcagni et al ( 33 ) explored the effects of mindfulness-based interventions on work engagement and demonstrated that the participants’ level of work engagement and performance successfully increased after interventions. Healthcare professionals who screened positive for depression were less engaged in their work.…”
Section: Discussionmentioning
confidence: 99%